Investigating English Education Master Students' Perceptions on Critical Thinking Skills - Kristian Florensio Wijaya (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
Abstract: One of the prominent and indispensable higher-order thinking skills that need to be fully mastered by EFL learners in this modern age is critical thinking. In the light of critical thinking skills, EFL learners are believed to be succeeded in both academic and real-life situations since they have become more strategic thinkers capable of managing their language learning enterprises. This small-scale qualitative study employed qualitative content analysis to fully obtain more renewable research findings influential for the betterment of ELT enterprises. Two research instruments were also harnessed to fulfill this major research objectivity namely the Likert-scale questionnaire and open-ended written narrative inquiry questions. The participants taking part voluntarily in this study were 15 English Education Master Students of Sanata Dharma University, Yogyakarta. Based on the obtained findings, two specific themes could be attained namely (1) Critical thinking skills enabled EFL learners to attain more fruitful target language learning outcomes, and (2) Critical thinking skills allowed EFL learners to be more life-long knowledge seekers. To holistically promote a higher degree of critical thinking skills for diverse EFL learners, language educators in this archipelago are strongly advocated to sustainably instill more engaging, meaningful, and contextual learning dynamics.  Keywords: critical thinking skills, English Education Master Students, qualitative   content analysis